Wrocław: image of the city in the years 1997-2007. Places liked and disliked. - Damurski, Łukasz (Bulletin of Geography. Socio-economic Series, 2007)
The image of a city can be a subject of various academic disciplines, such as urban sociology, psychology or marketing. This article presents preliminary findings of socio-spatial research conducted in Wrocław, Poland in the years 1997 and 2007. The study shows that the image of the city changes quite slowly compared to the rapid development of the landscape. The most liked and disliked places remained generally the same during the considered period, notwithstanding the improving quality of built-up areas. The main difference arises in the average number of answers given by each respondent, suggesting that the general attitude towards the city becomes more critical.